커뮤니케이션 의도와 주행 시나리오에 따른 자율주행차량 eHMI 디자인 컨셉 제안 - 송지훈(Jihoon Song); 기정민(Jeongmin Ki); 정이훈(Yihun Jeong); 황동욱(Dongwook Hwang) (디지털콘텐츠학회논문지, 2024)
자율주행 기술의 진보로 인해 차량 내 운전자의 역할이 점차 줄어들면서 기존 차량에서 수행되어 오던 전통적인 차량-보행자 간 정보 전달 체계에 대한 변화 가능성이 제기되고 있다. 현재까지 자율주행차량 시스템과 외부와의 커뮤니케이션을 위해 인간-기계 인터페이스를 통한 다양한 신호를 외부에 전달하는 방법이 제안되고 있지만, 최적의 커뮤니케이션 방식에 대한 합의는 아직 이루어지지 않고 있다. 본 연구는 자율주행차량과 보행자와의 커뮤니케이션을 위한 다양한 인간-기계 인터페이스 설계안을 제시하고, 자율주행차량의 커뮤니케이션 의도와 주행 시나리오에 따라 이를 검증하는 것을 목표로 한다. 연구 결과, 자율주행차량의 주행 시나리오에 따라 인터페이스 유형과 색상이 보행자의 실용성, 직관성, 선호도 측면에서 유의미하게 영향을 미치는 것으로 나타났다. The evolution of autonomous driving technology has resulted in a gradual diminishment of the role of drivers within vehicles, prompting potential alterations to the traditional vehicle-pedestrian communication system employed by conventional vehicles. Various methods employing human-machine interfaces (HMIs) to convey signals to the external environment for communication between autonomous vehicles and the external world have been proposed. However, consensus on the most effective communication method has not yet been reached. This study aims to develop and validate diverse HMI design concepts for autonomous vehicles, with a focus on communication with pedestrians, taking into account the vehicle’s communication intention and various driving scenarios. The research findings indicate that, depending on the autonomous driving scenarios, the design and color of interfaces significantly influence pedestrian perceptions of usefulness, trust, and preference. KCI Citation Count: 2